2021
DOI: 10.1371/journal.pone.0251608
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among isolated teratozoospermia, sperm DNA fragmentation and markers of systemic inflammation in primary infertile men

Abstract: Aim To assess the prevalence of isolated teratozoospermia (iTZS) in a cohort of infertile and fertile men; explore the relationship between iTZS, inflammatory parameters and sperm DNA fragmentation index (SDF) in the same cohort. Materials and methods 1824 infertile men and 103 fertile controls. Semen analysis, the neutrophil-to-lymphocyte ratio (NLR) and serum hormones were investigated. DFI was tested in infertile men only. According to 2010 WHO semen analysis, patients were categorized in 3 sub-groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
1
11
0
1
Order By: Relevance
“…Finally, although an association between impaired renal function and semen parameters was not observed, we did not examine alterations in the sperm quality profile that could be even more sensitive to alterations in the state of overall men's health, such as an increase in the percentage of sperm DNA fragmentation. [42][43][44] In addition, we included a very selected group of infertile men, that is, those with availability of eGFR evaluation in a tertiary referral center; therefore, the study of association of putative risk factors such as impaired kidney function with impaired semen analysis might be biased by information and selection bias. Further studies with larger cohorts are certainly needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, although an association between impaired renal function and semen parameters was not observed, we did not examine alterations in the sperm quality profile that could be even more sensitive to alterations in the state of overall men's health, such as an increase in the percentage of sperm DNA fragmentation. [42][43][44] In addition, we included a very selected group of infertile men, that is, those with availability of eGFR evaluation in a tertiary referral center; therefore, the study of association of putative risk factors such as impaired kidney function with impaired semen analysis might be biased by information and selection bias. Further studies with larger cohorts are certainly needed.…”
Section: Discussionmentioning
confidence: 99%
“…Third, for the definition of CKD, we used the threshold set by the KDIGO guidelines (i.e., defining kidney function impairment as eGFR < 90 mL/min per 1.73 m 2 and CKD as eGFR < 60 mL/min per 1.73 m 2 ); however, evidence exists that the threshold for CKD should be set at higher eGFR levels for younger individuals, 41 thus potentially increasing the proportion of men with initial kidney function impairment among young men with primary infertility. Finally, although an association between impaired renal function and semen parameters was not observed, we did not examine alterations in the sperm quality profile that could be even more sensitive to alterations in the state of overall men's health, such as an increase in the percentage of sperm DNA fragmentation 42–44 . In addition, we included a very selected group of infertile men, that is, those with availability of eGFR evaluation in a tertiary referral center; therefore, the study of association of putative risk factors such as impaired kidney function with impaired semen analysis might be biased by information and selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that the prevalence of isolated teratozoospermia may be more prevalent in fertile controls compared to infertile men. 16 We questioned eight heterozygote females from our study (F1:IV-1, IV-3, and V-5; F2:II- Kaposi sarcoma is caused by Kaposi sarcoma herpesvirus/human herpesvirus 8 (KSHV/HHV8) infection. Most people may have KSHV/ HHV8 in their system and they do not develop Kaposi sarcoma unless their immune system is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Semen analyses were based on 2010 WHO reference criteria 14 : oligozoospermia was defined as <15 million spermatozoa per ml; asthenozoospermia as <32% progressive motility; and teratozoospermia <4% of typical forms 19 . Sperm DNA fragmentation (SDF) index was measured by sperm chromatin structure assay 20 …”
Section: Methodsmentioning
confidence: 99%